Pengaruh Latihan Beban Menggunakan Dumbbel Terhadap Kecepatan Pukulan Kizame Tsuki Atlit Karate Inkanas SMPN 30 Makassar - Reskiyana, Hani Sucita Nur; Pallawagau, Andi; Isman, Muhammad; Hasan, Hamka; Hidayat, Rahmat; Arfanda, Poppy Elisano (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the effect of weight training using dumbbells on Kizame Tsuki's punching speed at Inkanas Karate Athlete at SMPN 30 Makassar. This research is experimental research. The population used in this research were all Inkanas Karate Athletes at SMPN 30 Makassar. The number of samples was taken as a saturated sample with a sample of 20 male athletes divided into 2 groups, namely 10 athletes in the experimental group and 10 athletes in the control group. The data collection technique uses a survey method, namely tests and measurements with instruments in the form of measuring Kizame Tsuki's punch speed in karate sports. The data analysis technique uses descriptive analysis of percentage frequencies, t test analysis through prerequisite tests for normality and linearity. The results of this research show that; Analysis of the effect of dumbbell training on the punching speed of Kizame Tsuki karate athletes at Inkanas SMPN 30 Makassar, obtained a value of t = -5.783 (P=.000 <  0.05), then H0 is rejected and H1 is accepted, meaning there is a significant effect of dumbbell training on punching speed Kizame Tsuki, karate athlete at Inkanas SMPN 30 Makassar.